Toughened modified nitrile rubber and preparation method thereof
Nanomolybdenum oxide hybrid magnesium hydroxide and biomass cellulose nanocrystals were prepared by using hydrothermal method in nitrile rubber, and vanillin-based phosphorus-nitrogen synergistic flame retardant was used to solve the wear resistance and flame retardant of nitrile rubber. The performance deficiency has achieved the preparation of toughened modified nitrile rubber with high flame retardant and high wear resistance, expanding its application range.
Patent Information
- Application Number
- CN202411693089.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-10
AI Technical Summary
The defects of nitrile rubber in wear resistance and flame retardant properties limit their application scope, and the prior art is difficult to effectively improve these defects.
By optimizing the formulation and process, nanomolybdenum oxide hybrid magnesium hydroxide and biomass cellulose nanocrystals were prepared by hydrothermal method, and modified with vanillin-based phosphorus-nitrogen synergistic flame retardant to improve the flame retardancy of nitrile rubber and mechanical strength.
A toughened modified nitrile rubber with green and environmental protection, good toughness, high flame retardant and high wear resistance was prepared, which significantly expanded its application range.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber, in particular to a toughened modified nitrile rubber and a preparation method thereof. Background Art
[0002] Rubber materials are widely used in electronics, machinery, chemical industry and other fields, such as in wires and cables, conveyor belts, adhesives, hoses, gaskets, sealing materials and other industries. Nitrile rubber, which has excellent heat resistance, electrical insulation and chemical stability, is one of the commonly used synthetic rubbers. With the rapid development of science and technology, the requirements for nitrile rubber are getting higher and higher.
[0003] The defects of nitrile rubber in wear resistance and flame retardancy limit its application. Therefore, it is an important means to improve the various defects of nitrile rubber by modifying it with other polymer materials or adding fillers. Summary of the invention
[0004] The object of the present invention is to provide a toughened modified nitrile rubber and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing toughened modified nitrile rubber comprises the following steps:
[0007] The nitrile rubber is put into an internal mixer, and then composite magnesium hydroxide, an activator, modified cellulose nanocrystals and an antioxidant are added in sequence, mixed, discharged to form a rubber compound, which is then transferred into an open mixer, rolled, and then a vulcanizing agent and an accelerator are added, filtered, produced into sheets, left to stand for treatment, and vulcanized to obtain a toughened modified nitrile rubber.
[0008] Furthermore, the activator is a compound of nano zinc oxide and stearic acid in a mass ratio of 2:1.
[0009] Furthermore, the vulcanizing agent is one or a combination of sulfur, ethylene thiourea, diisopropylbenzene peroxide, di-o-tolylguanidine, and ethyl formate.
[0010] Furthermore, the accelerator is a sulfenamide accelerator.
[0011] Furthermore, the raw materials of the toughened modified nitrile rubber are, by weight: 100 parts of nitrile rubber, 4-7 parts of activator, 7-13 parts of composite magnesium hydroxide, 3-7 parts of modified cellulose nanocrystals, 1-3 parts of antioxidant, 1-5 parts of vulcanizer, and 0.8-2.2 parts of accelerator.
[0012] Further, the preparation of composite magnesium hydroxide comprises the following steps:
[0013] (1) ammonium molybdate and deionized water are mixed, magnesium hydroxide is added, and the mixture is transferred to a reaction kettle, kept at 158-162° C. for 9-11 hours, filtered, washed, and dried to obtain hybrid magnesium hydroxide;
[0014] (2) mixing hybrid magnesium hydroxide and isopropanol, adding a mixed solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, deionized water and ethanol, keeping the mixture at 80-90° C. for 4-5 hours, centrifuging, washing and drying to obtain epoxidized hybrid magnesium hydroxide;
[0015] (3) In a nitrogen atmosphere, epoxidized hybrid magnesium hydroxide, vanillin-based phosphorus-nitrogen synergistic flame retardant, and dimethyl sulfoxide are mixed, heated to 100-110° C. and kept warm for 5-6 hours, cooled, washed, and dried to obtain composite magnesium hydroxide.
[0016] Further, the preparation of modified cellulose nanocrystals comprises the following steps:
[0017] 1) Mix cellulose and sulfuric acid solution, stir at 43-47° C. for 2-3 hours, add deionized water, centrifuge, repeat adding water and centrifuging 3-5 times, put into dialysis bag, dialyze with deionized water until neutral, and obtain cellulose nanocrystal suspension; mix cellulose nanocrystal suspension and sodium periodate, adjust pH to 3, stir at 38-42° C. in dark for 3-4 hours, centrifuge, wash, dialyze, and dry to obtain dialdehyde cellulose nanocrystals;
[0018] 2) Mix the vanillin-based phosphorus-nitrogen synergistic flame retardant, acetic acid, and ethanol, stir at 18-25° C. for 20-30 minutes, add a mixed solution of dialdehyded cellulose nanocrystals and ethanol, keep warm at 58-62° C. for 18-20 hours, cool, adjust the pH value to 7, filter, wash, and dry to obtain modified cellulose nanocrystals.
[0019] Furthermore, the mass ratio of the vanillin-based phosphorus-nitrogen synergistic flame retardant and the dialdehyde-modified cellulose nanocrystals is 3:1.4.
[0020] Furthermore, the preparation of the vanillin-based phosphorus-nitrogen synergistic flame retardant comprises the following steps:
[0021] A. Under a nitrogen atmosphere, vanillin, triethylamine and ethyl acetate are mixed, cooled to 0°C, a mixture of phenylphosphonic dichloride and ethyl acetate is added, the temperature is raised to 58-62°C and kept warm for 22-24 hours, filtered, washed, dried, concentrated and recrystallized to obtain a phosphorus-containing dialdehyde intermediate;
[0022] B. Mix melamine, dimethyl sulfoxide and 1,2-cyclohexanedicarboxylic anhydride, heat to 118-122°C and keep warm for 3-4 hours, pour into sodium bicarbonate aqueous solution, stir at 18-25°C for 18-22 minutes, filter and dry to obtain cyclic imidized melamine;
[0023] C. Mix the phosphorus-containing dialdehyde intermediate, cyclic imide melamine and anhydrous ethanol, keep the mixture at 58-62°C for 6-8 hours, add a mixture of DOPO and anhydrous ethanol, raise the temperature to 78-82°C and keep the mixture for 11-12 hours, rotary evaporate, rinse with cold ethanol and deionized water for 3-5 times, and dry to obtain a vanillin-based phosphorus-nitrogen synergistic flame retardant.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The invention provides a toughened modified nitrile rubber and a preparation method thereof. By optimizing the formula and process, a green, environmentally friendly, tough, highly flame-retardant and highly wear-resistant toughened modified nitrile rubber is prepared, thereby greatly improving the application scope of the nitrile rubber.
[0026] In the present invention, based on the flame retardant requirements of materials, easily available, environmentally friendly and halogen-free magnesium hydroxide is selected as a flame retardant. In order to solve the problems of low flame retardant efficiency and poor smoke suppression effect when it is added alone, nano molybdenum oxide hybrid magnesium hydroxide is prepared by a hydrothermal method, thereby improving the flame retardant and smoke suppression effect of magnesium hydroxide. In order to improve the compatibility of the hybrid magnesium hydroxide with nitrile rubber, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is first used to epoxidize it, and then the epoxy-amino reaction is used to graft the vanillin-based phosphorus-nitrogen synergistic flame retardant, so that the flame retardancy of the nitrile rubber is improved while the mechanical strength of the nitrile rubber is greatly improved.
[0027] Vanillin-based phosphorus-nitrogen synergistic flame retardant is made of bio-based vanillin as raw material. It is first synthesized with phenylphosphonic dichloride to form a phosphorus-containing dialdehyde intermediate as a precursor, and then condensed with cyclic imidized melamine and then added with DOPO. The cyclic imidized melamine is prepared from melamine and 1,2-cyclohexanedicarboxylic anhydride, thereby greatly improving the flame retardant effect and toughness of the material.
[0028] In order to further improve the wear resistance of nitrile rubber, green biomass raw material cellulose nanocrystals are used to strengthen and toughen nitrile rubber, and the sodium periodate oxidation method is used to prepare dialdehyde cellulose nanocrystals. Then, the aldehyde-amino reaction is used to graft vanillin-based phosphorus-nitrogen synergistic flame retardant. While improving the dispersion uniformity of cellulose nanocrystals in nitrile rubber, the flame retardancy of the material is further improved, thereby greatly expanding the application range of nitrile rubber. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0031] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0032] Embodiment 1: A method for preparing a toughened modified nitrile rubber, comprising the following steps:
[0033] The nitrile rubber is put into an internal mixer, and then composite magnesium hydroxide, an activator, modified cellulose nanocrystals, and an antioxidant are added in sequence, mixed, discharged, and a rubber compound is formed, which is then transferred into an open mixer, rolled, and then a vulcanizing agent and an accelerator are added, filtered with a 50-mesh filter, produced into sheets, left to stand for treatment, and vulcanized to obtain a toughened modified nitrile rubber;
[0034] The activator is prepared by mixing nano zinc oxide and stearic acid in a mass ratio of 2:1;
[0035] The vulcanizing agent is sulfur; the accelerator is a sulfenamide accelerator;
[0036] The raw materials of the toughened modified nitrile rubber are as follows: 100 parts of nitrile rubber, 4 parts of activator, 7 parts of composite magnesium hydroxide, 3 parts of modified cellulose nanocrystals, 1 part of antioxidant, 1 part of vulcanizing agent, and 0.8 parts of accelerator.
[0037] The preparation of the composite magnesium hydroxide comprises the following steps:
[0038] (1) ammonium molybdate is added with deionized water to prepare an ammonium molybdate solution with a concentration of 0.035 mol / L, 2.03 g of magnesium hydroxide is added, the solution is transferred to a reaction kettle, the solution is kept at 158° C. for 11 h, the solution is filtered, washed and dried to obtain hybrid magnesium hydroxide;
[0039] (2) 3 g of hybrid magnesium hydroxide and 100 mL of isopropanol were mixed, and a mixture of 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 5 mL of deionized water and 55 mL of ethanol was added, and the mixture was kept at 80° C. for 5 h, centrifuged, washed and dried to obtain epoxidized hybrid magnesium hydroxide;
[0040] (3) Under a nitrogen atmosphere, 2.8 g of epoxidized hybrid magnesium hydroxide, 3.4 g of vanillin-based phosphorus-nitrogen synergistic flame retardant, and 50 mL of dimethyl sulfoxide were mixed, heated to 100 ° C. for 6 h, cooled, washed, and dried to obtain composite magnesium hydroxide;
[0041] The preparation of the vanillin-based phosphorus-nitrogen synergistic flame retardant comprises the following steps:
[0042] A. Under nitrogen atmosphere, 3 g of vanillin, 2 g of triethylamine and 20 mL of ethyl acetate were mixed, cooled to 0°C, a mixture of 2 g of phenylphosphonic dichloride and 8 mL of ethyl acetate was added, the temperature was raised to 58°C and kept warm for 24 h, filtered, washed, dried, concentrated and recrystallized to obtain a phosphorus-containing dialdehyde intermediate;
[0043] B. Mix 2.5 g of melamine, 20 mL of dimethyl sulfoxide, and 6.2 g of 1,2-cyclohexanedicarboxylic anhydride, heat to 118°C and keep warm for 4 hours, pour into 50 mL of 5% sodium bicarbonate aqueous solution, stir at 18°C for 22 minutes, filter and dry to obtain cyclic imidized melamine;
[0044] C. 4.2 g of phosphorus-containing dialdehyde intermediate, 3 g of cyclic imide melamine, and 40 mL of anhydrous ethanol were mixed, kept at 58 ° C for 8 h, 4.3 g of DOPO and 25 mL of anhydrous ethanol were added, the temperature was raised to 78 ° C for 12 h, rotary evaporation was performed, and the mixture was washed with cold ethanol and deionized water for 3 times, and dried to obtain a vanillin-based phosphorus-nitrogen synergistic flame retardant;
[0045] The preparation of the modified cellulose nanocrystals comprises the following steps:
[0046] 1) 0.9 g of cellulose and 16 mL of 600 g / L sulfuric acid solution were mixed, stirred at 43 °C for 3 h, 16 mL of deionized water was added, centrifuged for 5 min, the mixture was centrifuged 3 times, the mixture was loaded into a dialysis bag with a molecular weight cutoff of 10,000 Da, and dialyzed with deionized water until neutral to obtain a cellulose nanocrystal suspension with a mass concentration of 15 g / L; 1 g of sodium periodate was added to 50 mL of the cellulose nanocrystal suspension with a mass concentration of 15 g / L, the pH was adjusted to 3, the mixture was stirred at 38 °C in the dark for 4 h, centrifuged, washed, dialyzed, and dried to obtain dialdehyde cellulose nanocrystals;
[0047] 2) Mix 3 g of vanillin-based phosphorus-nitrogen synergistic flame retardant, 60 mL of 10% acetic acid, and 20 mL of anhydrous ethanol, stir at 18 ° C for 30 min, add a mixed solution of 1.4 g of dialdehyded cellulose nanocrystals and 10 mL of ethanol, keep warm at 58 ° C for 20 h, cool, adjust the pH value to 7, filter, wash, and dry to obtain modified cellulose nanocrystals.
[0048] Embodiment 2: A method for preparing a toughened modified nitrile rubber, comprising the following steps:
[0049] The nitrile rubber is put into an internal mixer, and then composite magnesium hydroxide, an activator, modified cellulose nanocrystals, and an antioxidant are added in sequence, mixed, discharged, and a rubber compound is formed, which is then transferred into an open mixer, rolled, and then a vulcanizing agent and an accelerator are added, filtered with a 50-mesh filter, produced into sheets, left to stand for treatment, and vulcanized to obtain a toughened modified nitrile rubber;
[0050] The activator is prepared by mixing nano zinc oxide and stearic acid in a mass ratio of 2:1;
[0051] The vulcanizing agent is sulfur; the accelerator is a sulfenamide accelerator;
[0052] The raw materials of the toughened modified nitrile rubber are as follows: 100 parts of nitrile rubber, 5 parts of activator, 11 parts of composite magnesium hydroxide, 5 parts of modified cellulose nanocrystals, 2 parts of antioxidant, 3 parts of vulcanizing agent, and 1.5 parts of accelerator.
[0053] The preparation of the composite magnesium hydroxide comprises the following steps:
[0054] (1) ammonium molybdate is added with deionized water to prepare an ammonium molybdate solution with a concentration of 0.035 mol / L, 2.03 g of magnesium hydroxide is added, the solution is transferred to a reaction kettle, the solution is kept at 160° C. for 10 h, the solution is filtered, washed and dried to obtain hybrid magnesium hydroxide;
[0055] (2) 3 g of hybrid magnesium hydroxide and 100 mL of isopropanol were mixed, and a mixture of 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 5 mL of deionized water and 55 mL of ethanol was added, and the mixture was kept at 85° C. for 4.5 h, centrifuged, washed and dried to obtain epoxidized hybrid magnesium hydroxide;
[0056] (3) Under a nitrogen atmosphere, 2.8 g of epoxidized hybrid magnesium hydroxide, 3.4 g of vanillin-based phosphorus-nitrogen synergistic flame retardant, and 50 mL of dimethyl sulfoxide were mixed, heated to 105° C. for 5.5 h, cooled, washed, and dried to obtain composite magnesium hydroxide;
[0057] The preparation of the vanillin-based phosphorus-nitrogen synergistic flame retardant comprises the following steps:
[0058] A. Under nitrogen atmosphere, 3 g of vanillin, 2 g of triethylamine and 20 mL of ethyl acetate were mixed, cooled to 0°C, a mixture of 2 g of phenylphosphonic dichloride and 8 mL of ethyl acetate was added, the temperature was raised to 60°C and kept for 23 h, filtered, washed, dried, concentrated and recrystallized to obtain a phosphorus-containing dialdehyde intermediate;
[0059] B. Mix 2.5 g of melamine, 20 mL of dimethyl sulfoxide, and 6.2 g of 1,2-cyclohexanedicarboxylic anhydride, heat to 120°C and keep warm for 3.5 h, pour into 50 mL of 5% sodium bicarbonate aqueous solution, stir at 20°C for 20 min, filter and dry to obtain cyclic imidized melamine;
[0060] C. 4.2 g of phosphorus-containing dialdehyde intermediate, 3 g of cyclic imide melamine, and 40 mL of anhydrous ethanol were mixed, kept at 60°C for 7 h, 4.3 g of DOPO and 25 mL of anhydrous ethanol were added, the temperature was raised to 80°C and kept for 11.5 h, rotary evaporated, rinsed with cold ethanol and deionized water 4 times in sequence, and dried to obtain a vanillin-based phosphorus-nitrogen synergistic flame retardant;
[0061] The preparation of the modified cellulose nanocrystals comprises the following steps:
[0062] 1) 0.9 g of cellulose and 16 mL of 600 g / L sulfuric acid solution were mixed, stirred at 45 °C for 2.5 h, 16 mL of deionized water was added, centrifuged for 5 min, the mixture was centrifuged 4 times, and the mixture was placed in a dialysis bag with a molecular weight cutoff of 10,000 Da, and dialyzed with deionized water until neutral to obtain a cellulose nanocrystal suspension with a mass concentration of 15 g / L; 1 g of sodium periodate was added to 50 mL of the cellulose nanocrystal suspension with a mass concentration of 15 g / L, the pH was adjusted to 3, stirred at 40 °C in the dark for 3.5 h, centrifuged, washed, dialyzed, and dried to obtain dialdehyde cellulose nanocrystals;
[0063] 2) Mix 3 g of vanillin-based phosphorus-nitrogen synergistic flame retardant, 60 mL of 10% acetic acid, and 20 mL of anhydrous ethanol, stir at 20 ° C for 25 min, add a mixed solution of 1.4 g of dialdehyded cellulose nanocrystals and 10 mL of ethanol, keep warm at 60 ° C for 19 h, cool, adjust the pH value to 7, filter, wash, and dry to obtain modified cellulose nanocrystals.
[0064] Embodiment 3: A method for preparing a toughened modified nitrile rubber, comprising the following steps:
[0065] The nitrile rubber is put into an internal mixer, and then composite magnesium hydroxide, an activator, modified cellulose nanocrystals, and an antioxidant are added in sequence, mixed, discharged, and a rubber compound is formed, which is then transferred into an open mixer, rolled, and then a vulcanizing agent and an accelerator are added, filtered with a 50-mesh filter, produced into sheets, left to stand for treatment, and vulcanized to obtain a toughened modified nitrile rubber;
[0066] The activator is prepared by mixing nano zinc oxide and stearic acid in a mass ratio of 2:1;
[0067] The vulcanizing agent is sulfur; the accelerator is a sulfenamide accelerator;
[0068] The raw materials of the toughened modified nitrile rubber are as follows: 100 parts of nitrile rubber, 7 parts of activator, 13 parts of composite magnesium hydroxide, 7 parts of modified cellulose nanocrystals, 3 parts of antioxidant, 5 parts of vulcanizing agent, and 2.2 parts of accelerator.
[0069] The preparation of the composite magnesium hydroxide comprises the following steps:
[0070] (1) ammonium molybdate is added with deionized water to prepare an ammonium molybdate solution with a concentration of 0.035 mol / L, 2.03 g of magnesium hydroxide is added, the solution is transferred to a reaction kettle, the solution is kept at 162° C. for 9 h, the solution is filtered, washed and dried to obtain hybrid magnesium hydroxide;
[0071] (2) 3 g of hybrid magnesium hydroxide and 100 mL of isopropanol were mixed, and a mixture of 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 5 mL of deionized water and 55 mL of ethanol was added, and the mixture was kept at 90° C. for 4 h, centrifuged, washed and dried to obtain epoxidized hybrid magnesium hydroxide;
[0072] (3) Under a nitrogen atmosphere, 2.8 g of epoxidized hybrid magnesium hydroxide, 3.4 g of vanillin-based phosphorus-nitrogen synergistic flame retardant, and 50 mL of dimethyl sulfoxide were mixed, heated to 110° C. for 5 h, cooled, washed, and dried to obtain composite magnesium hydroxide;
[0073] The preparation of the vanillin-based phosphorus-nitrogen synergistic flame retardant comprises the following steps:
[0074] A. Under nitrogen atmosphere, 3 g of vanillin, 2 g of triethylamine and 20 mL of ethyl acetate were mixed, cooled to 0°C, a mixture of 2 g of phenylphosphonic dichloride and 8 mL of ethyl acetate was added, the temperature was raised to 62°C and kept warm for 22 h, filtered, washed, dried, concentrated and recrystallized to obtain a phosphorus-containing dialdehyde intermediate;
[0075] B. Mix 2.5 g of melamine, 20 mL of dimethyl sulfoxide, and 6.2 g of 1,2-cyclohexanedicarboxylic anhydride, heat to 122°C and keep warm for 3 h, pour into 50 mL of 5% sodium bicarbonate aqueous solution, stir at 25°C for 18 min, filter and dry to obtain cyclic imidized melamine;
[0076] C. 4.2 g of phosphorus-containing dialdehyde intermediate, 3 g of cyclic imide melamine, and 40 mL of anhydrous ethanol were mixed, kept at 62°C for 6 h, 4.3 g of DOPO and 25 mL of anhydrous ethanol were added, the temperature was raised to 82°C and kept for 11 h, rotary evaporated, rinsed with cold ethanol and deionized water for 5 times, and dried to obtain a vanillin-based phosphorus-nitrogen synergistic flame retardant;
[0077] The preparation of the modified cellulose nanocrystals comprises the following steps:
[0078] 1) 0.9 g of cellulose and 16 mL of 600 g / L sulfuric acid solution were mixed, stirred at 47 ° C for 2 h, 16 mL of deionized water was added, centrifuged for 5 min, and the mixture was centrifuged 5 times. The mixture was placed in a dialysis bag with a molecular weight cutoff of 10,000 Da, and dialyzed with deionized water until neutral to obtain a cellulose nanocrystal suspension with a mass concentration of 15 g / L; 1 g of sodium periodate was added to 50 mL of the cellulose nanocrystal suspension with a mass concentration of 15 g / L, the pH was adjusted to 3, stirred at 42 ° C in the dark for 3 h, centrifuged, washed, dialyzed, and dried to obtain dialdehyde cellulose nanocrystals;
[0079] 2) Mix 3 g of vanillin-based phosphorus-nitrogen synergistic flame retardant, 60 mL of 10% acetic acid, and 20 mL of anhydrous ethanol, stir at 25 ° C for 20 min, add a mixed solution of 1.4 g of dialdehyded cellulose nanocrystals and 10 mL of ethanol, keep warm at 62 ° C for 18 h, cool, adjust the pH value to 7, filter, wash, and dry to obtain modified cellulose nanocrystals.
[0080] Comparative Example 1: Taking Example 3 as the control group, magnesium hydroxide was used to replace the composite magnesium hydroxide, and the other processes were normal.
[0081] Comparative Example 2: Taking Example 3 as the control group, cellulose nanocrystals were used to replace the modified cellulose nanocrystals, and other processes were normal.
[0082] Comparative Example 3: Example 3 was used as the control group, and the vanillin-based phosphorus-nitrogen synergistic flame retardant was not prepared, and the other processes were normal.
[0083] Source of raw materials (for demonstration only):
[0084] Nitrile rubber A00150: Wuhan Jiyesheng Chemical Co., Ltd.; antioxidant CurekindTMQ: Ningbo Aikemu New Materials Co., Ltd.; sulfur S-80: Guangzhou Wanchun Chemical Co., Ltd.; sulfonamide accelerator 4979-32-2: Hubei Rishengchang New Materials Technology Co., Ltd.; nano zinc oxide Z141332, stearic acid S424818, ammonium molybdate A116375, magnesium hydroxide M104278, γ-(2,3-epoxypropoxy)propyltrimethoxysilane G13440 7. Vanillin V100115, triethylamine T103285, phenylphosphonic dichloride P160250, melamine M108433, dimethyl sulfoxide D103272, 1,2-cyclohexanedicarboxylic anhydride C124721, DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) D102416, cellulose C104843: Aladdin reagent; sodium periodate, sodium bicarbonate, isopropanol, ethanol, ethyl acetate, sulfuric acid, acetic acid, analytical grade: Sinopharm reagent.
[0085] Performance test: The rubber prepared in the examples and comparative examples was tested for performance:
[0086] Impact strength: a 63mm×13mm×4mm specimen was made, a V-shaped notch was cut with a notching machine, and the notched impact strength was measured with reference to GB / T1043.1-2008; Flame retardancy: a horizontal vertical combustion tester was used to test the vertical combustion performance with reference to GB / T 10707-2008; Abrasion resistance: relative volume abrasion loss was tested with reference to GB / T9867-2008, and the test results are shown in Table 1;
[0087] Table 1
[0088] <![CDATA[Impact strength (KJ / m 2 )]]> Flame retardant grade <![CDATA[Relative volume wear (mm 3 )]]> Example 1 21.1 FV-0 109 Example 2 21.3 FV-0 108 Example 3 21.4 FV-0 106 Comparative Example 1 17.8 FV-1 119 Comparative Example 2 17.4 FV-1 125 Comparative Example 3 16.7 FV-2 130
[0089] The invention provides a toughened modified nitrile rubber and a preparation method thereof. By optimizing the formula and process, a green, environmentally friendly, tough, highly flame-retardant and highly wear-resistant toughened modified nitrile rubber is prepared, thereby greatly improving the application scope of the nitrile rubber.
[0090] Example 3 is compared with Comparative Example 1. In the present invention, based on the flame retardant requirements of the material, the easily available, environmentally friendly and halogen-free magnesium hydroxide is selected as the flame retardant. In order to solve the problems of low flame retardant efficiency and poor smoke suppression effect when it is added alone, nano-molybdenum oxide hybrid magnesium hydroxide is prepared by a hydrothermal method, thereby improving the flame retardant and smoke suppression effect of magnesium hydroxide. In order to improve the compatibility of the hybrid magnesium hydroxide with nitrile rubber, it is first epoxidized with γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and then the vanillin-based phosphorus-nitrogen synergistic flame retardant is grafted by epoxy-amino reaction, which greatly improves the mechanical strength of the nitrile rubber while improving the flame retardancy of the nitrile rubber.
[0091] Example 3 is compared with Comparative Example 2. In order to further improve the wear resistance of nitrile rubber, green biomass raw material cellulose nanocrystals are selected to strengthen and toughen the nitrile rubber, and the sodium periodate oxidation method is used to prepare dialdehyde cellulose nanocrystals. Then, the aldehyde-amino reaction is used to graft the vanillin-based phosphorus-nitrogen synergistic flame retardant. While improving the dispersion uniformity of cellulose nanocrystals in nitrile rubber, the flame retardancy of the material is further improved, thereby greatly expanding the scope of use of nitrile rubber.
[0092] Comparing Example 3 with Comparative Example 3, the vanillin-based phosphorus-nitrogen synergistic flame retardant is prepared by using bio-based vanillin as a raw material, firstly synthesizing a phosphorus-containing dialdehyde intermediate with phenylphosphonic dichloride as a precursor, and then condensing it with cyclic imide melamine and then adding it with DOPO, wherein the cyclic imide melamine is prepared from melamine and 1,2-cyclohexanedicarboxylic anhydride, thereby greatly improving the flame retardant effect and toughness of the material.
[0093] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a toughened modified nitrile rubber, characterized in that: The steps include: The nitrile rubber is put into an internal mixer, and then composite magnesium hydroxide, an activator, modified cellulose nanocrystals and an antioxidant are added in sequence, mixed, discharged to form a rubber compound, which is then transferred into an open mixer, rolled, and then a vulcanizing agent and an accelerator are added, filtered, produced into sheets, left to stand for treatment, and vulcanized to obtain a toughened modified nitrile rubber.
2. The method for preparing a toughened modified nitrile rubber according to claim 1, wherein: The activator is prepared by mixing nano zinc oxide and stearic acid in a mass ratio of 2:
1.
3. A method for preparing a toughened modified nitrile rubber according to claim 1, characterized in that: The vulcanizing agent is one or a combination of sulfur, ethylene thiourea, diisopropylbenzene peroxide, di-o-tolylguanidine and ethyl formate.
4. A method for preparing a toughened modified nitrile rubber according to claim 1, characterized in that: The accelerator is a sulfenamide accelerator.
5. The method for preparing a toughened modified nitrile rubber according to claim 1, characterized in that: The raw materials of the toughened modified nitrile rubber are as follows, by weight: 100 parts of nitrile rubber, 4-7 parts of activator, 7-13 parts of composite magnesium hydroxide, 3-7 parts of modified cellulose nanocrystals, 1-3 parts of antioxidant, 1-5 parts of vulcanizer and 0.8-2.2 parts of accelerator.
6. A method for preparing a toughened modified nitrile rubber according to claim 1, characterized in that: The preparation of the composite magnesium hydroxide comprises the following steps: (1) ammonium molybdate and deionized water are mixed, magnesium hydroxide is added, and the mixture is transferred to a reaction kettle, kept at 158-162° C. for 9-11 hours, filtered, washed, and dried to obtain hybrid magnesium hydroxide; (2) mixing hybrid magnesium hydroxide and isopropanol, adding a mixed solution of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, deionized water and ethanol, keeping the mixture at 80-90° C. for 4-5 hours, centrifuging, washing and drying to obtain epoxidized hybrid magnesium hydroxide; (3) In a nitrogen atmosphere, epoxidized hybrid magnesium hydroxide, vanillin-based phosphorus-nitrogen synergistic flame retardant, and dimethyl sulfoxide are mixed, heated to 100-110° C. and kept warm for 5-6 hours, cooled, washed, and dried to obtain composite magnesium hydroxide.
7. The method for preparing a toughened modified nitrile rubber according to claim 1, characterized in that: The preparation of the modified cellulose nanocrystals comprises the following steps: 1) Mix cellulose and sulfuric acid solution, stir at 43-47° C. for 2-3 hours, add deionized water, centrifuge, repeat adding water and centrifuging 3-5 times, put into dialysis bag, dialyze with deionized water until neutral, and obtain cellulose nanocrystal suspension; mix cellulose nanocrystal suspension and sodium periodate, adjust pH to 3, stir at 38-42° C. in dark for 3-4 hours, centrifuge, wash, dialyze, and dry to obtain dialdehyde cellulose nanocrystals; 2) Mix the vanillin-based phosphorus-nitrogen synergistic flame retardant, acetic acid, and ethanol, stir at 18-25° C. for 20-30 minutes, add a mixed solution of dialdehyded cellulose nanocrystals and ethanol, keep warm at 58-62° C. for 18-20 hours, cool, adjust the pH value to 7, filter, wash, and dry to obtain modified cellulose nanocrystals.
8. A method for preparing a toughened modified nitrile rubber according to claim 7, characterized in that: The mass ratio of vanillin-based phosphorus-nitrogen synergistic flame retardant and dialdehyded cellulose nanocrystals is 3:1.
4.
9. A method for preparing a toughened modified nitrile rubber according to claim 6 or 7, characterized in that: The preparation of the vanillin-based phosphorus-nitrogen synergistic flame retardant comprises the following steps: A. Under a nitrogen atmosphere, vanillin, triethylamine and ethyl acetate are mixed, cooled to 0°C, a mixture of phenylphosphonic dichloride and ethyl acetate is added, the temperature is raised to 58-62°C and kept warm for 22-24 hours, filtered, washed, dried, concentrated and recrystallized to obtain a phosphorus-containing dialdehyde intermediate; B. Mix melamine, dimethyl sulfoxide and 1,2-cyclohexanedicarboxylic anhydride, heat to 118-122°C and keep warm for 3-4 hours, pour into sodium bicarbonate aqueous solution, stir at 18-25°C for 18-22 minutes, filter and dry to obtain cyclic imidized melamine; C. Mix the phosphorus-containing dialdehyde intermediate, cyclic imide melamine and anhydrous ethanol, keep the mixture at 58-62°C for 6-8 hours, add a mixture of DOPO and anhydrous ethanol, raise the temperature to 78-82°C and keep the mixture for 11-12 hours, rotary evaporate, rinse with cold ethanol and deionized water for 3-5 times, and dry to obtain a vanillin-based phosphorus-nitrogen synergistic flame retardant.
10. A toughened modified nitrile rubber, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Cited By
Shaving board with antibacterial function and preparation process thereof
CN121340427A